An Empirical Study of the External Environmental Factors Influencing the Degree of Product Customization - Sandrin, Enrico (International Journal of Industrial Engineering and Management, 2016)
External environmental factors play a fundamental role in the strategic decisions a company intends to make, which in turn influence the organizational design choices. A widely known key strategic decision in the context of mass customization is the degree of product customization a firm provides to its customers. However, the impact of the external environment on the degree of product customization has yet to be empirically investigated. To narrow this research gap, the present paper empirically examines the impacts of three external environmental factors, namely competitive intensity, heterogeneity of customer demands, and dynamism of customer demands, on the degree of product customization, using survey data from 195 manufacturing plants in three industries and eight countries. Among the three examined factors, the paper identifies the dynamism of customer demands as a key factor that pushes firms to increase the degree of product customization they provide to their customers. Article history: Received (01.11.2016); Revised (24.11.2016); Accepted (20.12.2016)